2013
DOI: 10.2478/s13533-012-0147-2
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive history of the Barombi Mbo Maar, Cameroon Volcanic Line, Central Africa: Constraints from volcanic facies analysis

Abstract: his study presents the first and detail field investigations of exposed deposits at proximal sections of the Barombi Mbo Maar (BMM), NE Mt Cameroon, with the aim of documenting its past activity, providing insight on the stratigraphic distribution, depositional process, and evolution of the eruptive sequences during its formation. Field evidence reveals that the BMM deposit is about 126m thick, of which about 20m is buried lowermost under the lake level and covered by vegetation. Based on variation in pyroclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
(115 reference statements)
1
23
0
Order By: Relevance
“…A well-distinct 10 cm-thick paleosoil bed, which is indicative of relatively long quiescent period, separates the precedent units from the upper unit U 3 . From those observations, it was suggested that the BMM might be a polygenetic maar [7]. However, no systematic geochronological evidence existed to comfort that observation.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…A well-distinct 10 cm-thick paleosoil bed, which is indicative of relatively long quiescent period, separates the precedent units from the upper unit U 3 . From those observations, it was suggested that the BMM might be a polygenetic maar [7]. However, no systematic geochronological evidence existed to comfort that observation.…”
mentioning
confidence: 98%
“…Recently, from a tephrostratigraphic examination, the about Figure 1. Location map of the study area along the Cameroon volcanic line (A) and the geological map (B), modified after [7]. (C) shows the sampling points (stars) around the BMM and the adjacent maar, and the position of the limburgitic lava flow (black dot).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations